Beauvallet - Heyer, Georgette, 1902-1974 (Salt Lake City, UT : Project Gutenberg, 2025)
"Beauvallet" by Georgette Heyer is an adventure novel published in 1929. Sir Nicholas Beauvallet, a daring Elizabethan pirate known as "Mad Nick," plunders Spanish ships with the Queen's blessing. After capturing a galleon carrying the proud Doña Dominica, he vows to return and claim her as his bride. Disguised as a Frenchman, he ventures into hostile Catholic Spain to win her but must outwit jealous suitors, suspicious ambassadors, and the deadly Inquisition to escape with his chosen love. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Beauvallet
Release date is 2025-03-07
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Historical fiction; Love stories; Adventure stories; Pirates -- Fiction; Regency fiction; Nobility -- England -- Fiction